Gender in Agriculture Closing the Knowledge Gap - Quisumbing, Agnes R.; Quisumbing, Agnes R.; Meinzen-Dick, Ruth.; Meinzen-Dick, Ruth.; Raney, Terri L.; Raney, Terri L.; Croppenstedt, André.; Croppenstedt, André.; Behrman, Julia A.; Behrman, Julia A.; Peterman, Amber.; Peterman, Amber. (Springer Netherlands : Imprint: Springer, 2014)
The Food and Agriculture Organization of the United Nations (FAO) produced a 2011 report on women in agriculture with a clear and urgent message: agriculture underperforms because half of all farmers—women—lack equal access to the resources and opportunities they need to be more productive. This book builds on the report’s conclusions by providing, for a non-specialist audience, a compendium of what we know now about gender gaps in agriculture. The authors explore linkages among gender, assets, and agricultural development projects. They examine the current state of land tenure; women’s access to markets, financial services, and rural employment; and gender differences in social capital and in vulnerability to poor nutrition and health. The book also looks at trends in agricultural research, development, and extension systems and in women’s participation in research. The opening section summarizes the main messages of the 2011 FAO report and reviews how gender has been conceptualized in agriculture and how these concepts have changed in the past three decades. Topics covered include how demographic conditions such as household structure, age, and migration have affected gender relations. Part 2 of the book focuses on data and methods for understanding gender issues in agriculture. The authors look at changing institutional approaches to addressing gender and assess past and present methods for effectively collecting and analyzing data on gender roles and relations in agriculture. Part 3 gathers background studies that document gender gaps in assets and key agricultural inputs. Part 4 looks beyond the farm to observe and analyze gender roles in markets and value chains. Part 5 proposes ways that agricultural research, development, and extension systems can be made more responsive to the needs of both male and female farmers. The research findings collected here provide, in non-technical language, an overview of a pressing problem in agricultural development—the disadvantages and inequities that burden women farmers—as well as ways to understand and address this problem. Published with the Food and Agriculture Organization of the United Nations.